PENGARUH LIKUIDITAS, SOLVABILITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN PERBANKAN, ASURANSI & LEMBAGA KEUANGAN LAINNYA DI BURSA EFEK INDONESIA TAHUN 2010-2013 - Muhammad Fadhli; Kamaliah -; Julita - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims are to determine the significances effect of liquidity, leverage, profitability, dividend policy as moderation with the corporate’s value. The study population was 56 companies, but based on the criteria there are only 24 (thirty-four) companies. Sampling using purpossive sampling technique while data analysis using multiple linear regression model. The study states that the Loan to Deposit Ratio (LDR) significantly affects the corporate’s value. Debt to Equity Ratio (DER) has no significant effect to the corporate’s value. Return on Assets has a significant effect to the corporate’s value. Loan to Deposit Ratio (LDR) moderated by dividend policy has a significantly influence to the corporate’s value. Debt to Equity Ratio (DER) moderated by dividend policy no significant effect on the corporate’s value. Return on Assets moderated by dividend policy has a significantly influence to the corporate’s value.Keywords: Liquidity, Leverage, Profitability, Dividend Policy, and Corporate Values